2015
DOI: 10.1146/annurev-genet-120213-092023
|View full text |Cite
|
Sign up to set email alerts
|

A Uniform System for the Annotation of Vertebrate microRNA Genes and the Evolution of the Human microRNAome

Abstract: Although microRNAs (miRNAs) are among the most intensively studied molecules of the past 20 years, determining what is and what is not a miRNA has not been straightforward. Here, we present a uniform system for the annotation and nomenclature of miRNA genes. We show that fewer than a third of the 1,881 human miRBase entries, and only approximately 16% of the 7,095 metazoan miRBase entries, are robustly supported as miRNA genes. Furthermore, we show that the human repertoire of miRNAs has been shaped by periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
530
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 479 publications
(554 citation statements)
references
References 158 publications
8
530
0
2
Order By: Relevance
“…Serum and CSF xenomiR levels were also similar when considering only CSF from healthy individuals (χ 2 test, P-value = 0.476). To demonstrate that our findings are not biased by the choice of miRNA database, we repeated the analysis using only the highly curated miRNAs from MirGeneDB (Fromm et al 2015). For zebrafish, chicken, and mouse we find exactly the same amount of miRNAs reported using miRBase and MirGeneDB (Supplemental Fig.…”
Section: Xenomirs Are Commonly Present In Body Fluidssupporting
confidence: 52%
“…Serum and CSF xenomiR levels were also similar when considering only CSF from healthy individuals (χ 2 test, P-value = 0.476). To demonstrate that our findings are not biased by the choice of miRNA database, we repeated the analysis using only the highly curated miRNAs from MirGeneDB (Fromm et al 2015). For zebrafish, chicken, and mouse we find exactly the same amount of miRNAs reported using miRBase and MirGeneDB (Supplemental Fig.…”
Section: Xenomirs Are Commonly Present In Body Fluidssupporting
confidence: 52%
“…Given the regulatory divergence between the species studied here, it is perhaps not surprising that we observe very limited evolutionary conservation of sex-biased miRNA expression across species. In fact, we were not able to identify a single case in which an orthologous (Kozomara and Griffiths-Jones 2014;Fromm et al 2015) mature miRNA showed significant bias in the same direction and in the same somatic tissue in two species (Supplemental Fig. S5).…”
Section: Discussionmentioning
confidence: 92%
“…The 795 human and 502 mouse (Figure S1) pre-miRNAs satisfying at least 4 out of the 5 high-confidence criteria were defined as the FANTOM5 robust set, and the remaining 1076 human and 684 mouse pre-miRNAs as the permissive set (Table S4 and S5). The robust set encompasses 735 human and 438 mouse mature miRNAs, and covers more than 90% of the high-confidence pre-miRNAs in miRBase (Figures S2 and S3), 90% of miRNAs well-characterized in the scientific literature (Figure S4), as well as 91% (human) and 88% (mouse) of pre-miRNAs included in the manually curated MirGeneDB database 20 (Figure S5). …”
Section: Resultsmentioning
confidence: 99%